Estrategias Didácticas en el aprendizaje de Estudios Sociales en los estudiantes de octavo año de la Unidad Educativa “Hermano Miguel” - Albarracín Chávez, Rosa Marina (2021)
The present research work focused on the problem where students, in spite of finding in their classrooms a certain diversity of didactic strategies, these are routine and not very motivating, which generates apathy and disinterest in them to learn social sciences. The objective was to develop didactic strategies to improve learning in the subject of social studies. For this purpose, a methodological design framed in the quantitative paradigm was used, combined with the applied research modality and the type of explanatory research. 259 students, 3 teachers and 2 authorities of the Educational Unit participated. The main results obtained corroborated the use of participation as a strategy and, as regards didactic resources, graphic organizers are the most used, which is why visits or excursions are not frequently used, thus wasting the advantages offered by this resource. In view of this, a proposal was made to improve the teaching-learning process with the use of the didactic resource of guided visits to interactive museums through micro-curricular planning, which has been validated by specialists and users, determining its feasibility. With the application of the proposal, 98% of the students make the visit, 90% understand the subject better, 86% are motivated to expand the content; 100% find paleontological and scientific museums interesting and 100% describe memories of positive emotions when visiting a virtual museum